Effects of praseodymium substitution on electrical properties of CaCu 3Ti4O12 ceramics - Rai A.K.; Gim J.; Shin E.-C.; Seo H.-H.; Mathew V.; Mandal K.D.; Parkash O.; Lee J.-S.; Kim J. (My University, 2025)
Effect of praseodymium (Pr3+) substitution at Ca2+ site in calcium copper titanate, CaCu3Ti4O12 (CCTO), has been investigated. Compositions with x=0.10 and 0.20 were synthesized in the system Ca(1-3x/2)PrxCu 3Ti4O12 by chemical route. Crystal structure is remained cubic. X-ray diffraction and field-emission scanning electron macrographs indicate the presence of secondary phases such as CaTiO3 and CuO. X-ray photoelectron spectroscopy suggests the substitution of Ca 2+ by Pr3+/Pr4+. Low temperature admittance spectroscopy identified two deep trapping levels at 0.098 and 0.073 eV for x=0.20 and 0.078 and 0.060 eV for x=0.10. High temperature impedance spectroscopy shows that the grain boundary potential is 0.40 eV and 0.48 eV for x=0.20 and x=0.10 samples respectively. Pr3+ doping decreases dielectric loss in the bulk at low temperature but increases the dc leakage due to the lower value of grain boundary potential. © 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.